Alguns estudos sobre a física de buracos negros regulares e singulares em cenários com nuvem e fluido de cordas e quintessência - Nascimento, Francinaldo Florencio do (2024)
In this thesis, we obtain and study some solutions of regular and singular black holes, with cloud and fluid of strings, and quintessence. We begin by briefly reviewing singular and regular black holes. We revisit the singular black holes of Schwarzschild and Reissner- Nordström, as well as the regular black holes of Bardeen, Hayward and Frolov, analyzing singularities, horizons, and thermodynamics. Next, we introduce the cloud and fluid of strings models that will be used as sources of gravitational fields. We then generalized the Bardeen, Hayward and Frolov solutions, considering multiple sources, with emphasis on the cloud of strings and the fluid of strings. The solutions obtained were analyzed in relation to the regularity and singularity of the metrics, with special attention to the role of the cloud and the fluid of strings in preserving the regularity of the solutions originally considered, namely those of Bardeen, Hayward and Frolov. In addition, the horizons, geodesics, effective potential and some aspects of thermodynamics of all the solutions obtained were investigated. Finally, an exact solution was found for a black hole in a scenario in which a non-linear electromagnetic field is coupled to Einstein gravity, in the presence of a cloud of strings and quintessence as sources. We study some aspects of the thermodynamics of the black hole thus obtained and show how these quantities depend on the presence of the cloud of strings and quintessence.